2018
DOI: 10.23865/arctic.v9.1336
|View full text |Cite
|
Sign up to set email alerts
|

Russia’s Ambivalent Status-Quo/Revisionist Policies in the Arctic

Abstract: Russia has been following an Arctic policy that is highly heterogeneous, combining efforts at preserving cooperation with Western neighbors with commitment to building up its own strength. Three distinct policy modes can be identified: realist/militaristic, institutional/cooperative, and diplomatic management. Each mode is based on a particular interpretation of Russia’s various interests in the High North/Arctic: nuclear/strategic, geopolitical, economic/energy-related, and symbolic. Examination of policy mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Moreover, the stated objectives of these conferences are in line with Russia's foreign policy objectives in the Arctic. 44 Despite the inclusion of international cooperation, there is a noteworthy expression of strategical positioning in these conference objectives. President Putin has repeatedly indicated that he wants Russia to become internationally recognized as a global power, and that an active Arctic presence can help achieve this.…”
Section: Conferences Established 2010-2013mentioning
confidence: 99%
“…Moreover, the stated objectives of these conferences are in line with Russia's foreign policy objectives in the Arctic. 44 Despite the inclusion of international cooperation, there is a noteworthy expression of strategical positioning in these conference objectives. President Putin has repeatedly indicated that he wants Russia to become internationally recognized as a global power, and that an active Arctic presence can help achieve this.…”
Section: Conferences Established 2010-2013mentioning
confidence: 99%
“…On occasions, the two countries fought wars – most notably, one that resulted in Sweden losing Finland to the Russian Empire in 1809. During the Cold War, the Nordics were strategically peripheral (Hyde-Price, 2018: 440); yet, in Baev’s (2018: 410) analysis, they have now become strategically important, due to the location of Russia’s main base for strategic submarines in the Kola Peninsula. This makes the High North central to both the US and Russia, as a key location for placement of early warning and missile defence systems.…”
Section: Introductionmentioning
confidence: 99%
“…Such a "topical and paradigmatic DNA analysis" will show what ideas inform Russian expert and official "talk" on the Arctic; the actual "walk"-real-life policies in the Arctic-is covered by another article in this thematic cluster. 12 In section 2, we explore how geopolitical traditions discernible in today's Russia inform expert narratives on the "retrieved" Arctic. In section 3, we turn to official geopolitical approaches, examining how questions concerning the Arctic have been dealt with in Russian official statements on foreign and security policy.…”
Section: Introductionmentioning
confidence: 99%